Kualitas Tidur dan Pola Tidur sebagai Predisposisi Postpartum Blues pada Primipara - Wahyuni Harahap; M.G. Adiyanti Adiyanti (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2017)
Background: Postpartum blues is thought to be a normal reponse after childbirth in the community. Due to that reason, this psychological disorder has not been managed well. Although mental disorder during postpartum period hasn’t understood well, pain after birth, fatigue, poor sleeping quality, anxiety for unabling to care for the newborn and changes in sleep patern have become risk factors for the development of postpartum blues.Objective: To understand to relationship between sleep pattern and quality of sleep in the development of postpartum blues in primiparas.Method: The subjects for the study were 45 primaras taken from 3 community health centers with in patients facilities in Yogyakarta city. The inclusion criteria were normal deliveries, both the mothers and her babies were healthy, the baby was less than 15 days old, and the mothers were 18 – 40 years old. The data were collected using questionnaires that measure the sleep pattern scale, the sleep quality’s scale and the postpartum blues’ scale. The datas were analyzed using path analysis.Result and Discussion: Sleep quality and sleep patern together influenced postpartum blues for 57,5% (p < 0,000). Sleep quality partially influenced postpartum blues for 41% (p < 0,01) and sleep pattern influenced postpartum blues for 33% (p < 0,05).Conclusion: Sleep quality and sleep pattern influenced the incidence of postpartum blues.Keywords: postpartum blues, sleep quality, sleep pattern, primipara